Representation Of Women's Masculinity In Somethinc And Batman Co-Branding Communication - Hazimah, Ayu Zahra; Venus, Anter (Jurnal Sains Sosio Humaniora, 2026)
The beauty industry increasingly employs co-branding strategies to strengthen brand positioning and attract consumer attention. One notable collaboration is Somethinc x Batman, which combines the identity of a beauty brand with a popular superhero franchise. Beyond its marketing function, this collaboration presents an interesting phenomenon regarding the representation of female masculinity through visual communication. This study aims to analyze the representation of female masculinity in the co-branding communication of Somethinc x Batman through a teaser video uploaded on the Instagram account @somethincmakeup. This research employed a descriptive qualitative approach with an interpretive paradigm and Roland Barthes’ semiotic analysis. The data were analyzed through the stages of denotative, connotative, and mythological meanings to identify visual signs representing female masculinity. The findings reveal that the Somethinc x Batman campaign represents women as dominant, brave, independent, rational, and self-controlled figures through sharp gazes, upright body posture, aggressive gestures, dark visual tones, and the symbolic attributes of Catwoman. However, the representation of masculinity does not entirely eliminate femininity, as it remains intertwined with beauty and sensuality associated with the cosmetic industry. This study concludes that female masculinity in beauty media is constructed through a negotiation between masculine and feminine attributes within popular culture and co-branding communication practices.